Results of parallel independent visual evaluation of projective cover of the bottom during macrophyte assesment survey - A. A. Dulenin (Известия ТИНРО)
A simple and cost-effective method for macrophyte stock assessment as visual survey, was tested. It demonstrated good efficiency for counting of Saccharina japonica. The method is based on visual evaluation of SAV projective cover. Such subjective data should be verified. For this purpose, the projective cover along the Tatar Strait coast was estimated independently by two observers. In total, 125 km of the coastline was surveyed with 322 parallel visual estimations at 81 stations. The estimations of both observers agreed well: the concordance coefficient was 0.73 for the total projective cover and 0.78 for the projective cover of S. japonica, at p < 0.0001. About 81 % of the total projective cover and 82 % of S. japonica projective cover were counted with high coherency, whereas poor coherency was noted for < 3 % of both parameters. Average difference between estimations of two observers was 0.083 ± 0.012 for the total projective cover and 0.090 ± 0.012 for S. japonica projective cover. However, comparison of the visual estimations from the sea surface with the SCUBA estimations made near the bottom showed that surface observations resulted in some underestimation of the total projective cover, though the difference was statistically insignificant (p = 0.68). The near-bottom SCUBA survey provides better assessment for small and cortical algae (Ralfsiales and partially Corallinales). Commercial stock of S. japonica was calculated using previously reported relationship between biomass and projective cover (r2 = 0.81). The stock estimations for certain areas on the data of two observers had no statistically significant differences (p = 0.46–0.80, depending on the criteria used), the total stock estimations were also very close (34 and 36 thousand tons for total stock and 26 and 24 thousand tons for its commercial part). The visual observations are useful for revealing general features of the vegetation spatial distribution. Linear regressions parameters of the algae abundance on latitude for the data of both observers were similar. They had the angular coefficients –0.13 ± 0.07 and –0.10 ± 0.07 for the total projective cover and –0.25 ± 0.07 and –0.23 ± 0.06 for S. japonica projective cover. In the southern part of survey, the average total projective cover was 0.59 ± 0.04, while it was slightly lower in the northern part: 0.53 ± 0.04; the same estimations for the projective cover of S. japonica differed more considerable: 0.49 ± 0.04 and 0.24 ± 0.03, respectively. There is concluded that the visual surveys of macrophytes are economically effective and allow to reduce labor efforts significantly, comparing with traditional SCUBA surveys (working time in 101 times, costs in 103 times). The video recording ensures the data verification by outside experts, as in the cases when observers cannot identify some species. However, capability of this method is limited by high water turbidity and other cases of worsened visibility. For successful implementation of visual surveys, its algorithm for various environmental conditions is developed and supplemented with necessary instructions.